Measuring leading placental edge to internal cervical os: Transabdominal versus transvaginal approach. Issue 4 (15th September 2017) - Westerway, Susan Campbell; Hyett, Jon; Henning Pedersen, Lars
Abstract: We aimed to compare the value of transabdominal (TA) and transvaginal (TV) approaches for assessing the risk of a low‐lying placenta. This involved a comparison of TA and TV measurements between the leading placental edge and the internal cervical os. We also assessed the intra‐/interobserver variation for these measurements and the efficacy of TA measures in screening for a low placenta. Methodology: Transabdominal and TV measurements of the leading placental edge to the internal cervical os were performed on 369 consecutive pregnancies of 16–41 weeks' gestation. The difference (TA‐TV) from the mean was calculated and plotted against gestational age. Bland‐Altman plots and paired t‐tests were used to look at the differences in TA/TV measurement. Screening performance of a transabdominal approach was compared to a transvaginal 'gold standard'. Nonparametric methods were used to calculate the area under the receiver operator characteristics (ROC) curve. Intra‐/interobserver variations were also calculated. Results: Of the pregnancies, 278 had a leading placental edge that was visible with the TV approach. Differences (TA‐TV) ranged from −50 mm to +57 mm. Bland‐Altman plot shows that TA measurements overestimated the distance compared with the TV measurements; the average difference in measurement was 12.0 mm (95% confidence interval 9.9–14.1). The sensitivity, specificity and negative predictive values of a TA approach were 18.2%, 97.5% and 87.2%, respectively. The receiver operator characteristics area between gestational weeks 16–23 was 0.81 (95% CI: 0.76–0.86). Conclusion: The TA approach has a low sensitivity for detecting a low‐lying placenta as choosing a TA cut‐off with sensitivity >90% will decrease the specificity to 50%.